Keabsahan HGB Sebagai Objek Hak Tanggungan Tanpa Persetujuan Pemegang Hak Pengelolaan - Fatimah Azzahra; Siti Nurul Intan Sari Dalimunthe (Jurnal USM Law Review)
This study have a purpose to review the validity of HGB as an object of mortgage rights and consequences of HGB as an object of mortgage rights without consent of holder of management rights. HGB is another type of land right, on top of the land management rights with the approval of the management rights holder, may be imposed with a mortgage. However, it is often found that HGB holders impose mortgage rights without the consent of management rights holders, so the legitimacy and legal consequences need to be questioned. Against this background it is important to carry out more analysis for the legality and legal consequences of HGB as an object of mortgage rights without the approval of holder of management rights. The applied research strategy uses a normative juridical with qualitative descriptive data analysis techniques and statute approach. The newness of this study is not only discuss how to imposition mortgage rights on HGB, but will also  discussion focused on validity and consequences if HGB as an object of mortgage rights is implemented out without consent of holder of management rights. The conclusion that can be cited from this discussion is that HGB as object of mortgage without consent of holder management rights does not have legal validity and as a result the imposition of mortgage rights can be requested for cancellation and can be null and void by law with a ruling from a court.